Individual differences in the inhibition of stimulus-stimulus and stimulus-response associations and medication effects on associative learning in Tourette syndrome and ADHD - Kantini, Ebrahim (2010)
Inhibition deficits have been the subject of intensive investigation in the context of ‘impulsivity’, both in relation to normal variation and clinical disorder. Until now the focus has been on inhibition of stimulus-response (S-R) associations, using tasks such as the Go/NoGo. However, a chain of antecedent stimuli may be important in the triggering of any particular response, which can thus depend on other aspects of the context beyond the immediately preceding stimulus. The present thesis therefore examines the inhibition of stimulus-stimulus (S-S) associations in both normal participants and participants with Attention Deficit Hyperactivity Disorder (ADHD) or Tourette syndrome (TS).